Comunicación digital para el posicionamiento de marca de la empresa Acme t-shirts & sweaters, cantón Ambato, provincia de Tungurahua - Freire Lema, Marco Alejandro (2025)
This thesis aims to investigate the impact of digital communication and marketing strategies on the brand positioning of ACME T-Shirts & Sweaters, a company operating in Ambato, Tungurahua province. Although the personalized fashion market has great potential for growth, ACME experiences numerous problems in external communication that result in limited visibility and interaction with customers. The lack of knowledge to segment its target audience and the lack of visualization of its products through digital media, result in a poor media performance, which is worrying since it is in a competitive environment. Keywords such as e-commerce and current trends in digital marketing are studied, highlighting the importance of the use of digital platforms and content marketing as important tools to catch the consumer's attention.